The use of textiles in the educational process at Waldorf primary schools - Mašát, Milan (Frontiers in Education, 2025)
This paper examines how textiles can be integrated into Waldorf primary schools through three exploratory case studies. Rather than prescribing guidelines, the study positions its outcomes within theoretical debates on craft, handwork, embodied knowing, and aesthetics. Drawing on interviews with three teachers, the cases illustrate that textiles can function both as cultural practices and as embodied engagements: they may support multisensory learning, strengthen patience and fine motor skills, and foster identity through imaginative and aesthetic experience. The analysis suggests that textiles are not merely peripheral activities but can serve as practices where cognition, embodiment, and self-understanding converge. Earlier perspectives, such as Stehlik’s critique of technology, are reconsidered considering current curriculum reforms that seek to balance digital tools with craft-based learning. The paper highlights the heuristic value of case studies for illustrating how theoretical concepts might be operationalized in practice, offering insights for academic discourse and pointing to future research on the intersection of material culture, pedagogy, and identity.